On some coefficient estimates for a class of p-valent functions - PROCA, Alexandrina Maria; RĂDUCANU, Dorina (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In this paper, we consider a class of p-valent functions. For functions in this class, we find sharp estimates for their first three coefficients. Upper bound for the second order, Hankel determinant is also obtained. Mathematics Subject Classification (2010): 30C45, 30C50. Received 29 August 2024; Accepted 10 January 2025.